Long-term follow up of workers exposed to solvents. Issue 2 (February 1990) - Edling, C; Ekberg, K; Ahlborg, G; Alexandersson, R; Barregård, L; Ekenvall, L; Nilsson, L; Svensson, B G
Abstract : Long term occupational exposure to organic solvents may cause adverse effects to the central nervous system. This collaborative study between six Swedish departments of occupational medicine examines the overall prognosis in terms of working capacity, symptoms, and psychometric test performance for individuals occupationally exposed to organic solvents. After re-analyses of the data from an initial clinical investigation of 111 men, the subjects were divided into two subgroups: one group of 65 with symptoms but no impairment on the tests and one group of 46 with toxic encephalopathy (symptoms and test impairment). At least five years after the initial examination the subjects were asked to attend a re-examination that included a structured medical interview and a psychometric investigation. The results indicate that effects on the central nervous system persist even when exposure has ceased. In the group of 46 more men had stopped working and were receiving sickness or early retirement pensions. This group also had reduced activity levels with regard to everyday life, leisure activities, and education or training and more neuropsychiatric symptoms. There was no support for the view that a solvent induced toxic encephalopathy is a progressive disease comparable with presenile dementia such as Alzheimer's disease or Pick's disease. If a worker was removed from exposure when he presented symptoms without signs of impairment in intellectual function recovery was seen in most cases.